CAPITAL ADEQUACY RATIO (CAR) DAN DANA PIHAK KETIGA (DPK) TERHADAP RETURN ON ASSET (ROA) DENGAN PENYALURAN KREDIT SEBAGAI VARIABEL INTERVENING - P Haryoso; Bambang Kusdiasmo (ADVANCE, 2017)
This research aimed to determine the influence of Capital Adequacy Ratio (CAR) and third party funds (DPK) througt landing. The influence of Capital Adequacy Ratio (CAR),  third party funds (DPK), and the distribution credit for Return on Asset (ROA). The influence Capital Adequacy Ratio (CAR) about Return on Asset (ROA) througt landing . third party funds (DPK) about Return on Asset (ROA) througt landing. The Population in this study all commercial banks in Indonesia are listed on the Stock Exchange the period of 2012-2015. The samples based on purposive sampling are 15 commercial banks in Indonesia -year period 2012-2015. Data is taken from secondary data from company financial statements of Commercial Bank and listed on the Indonesia Stock Exchange. Data analysis methods used in the study were multiple linier regression analysis, with descriptive statistics test , linearity test , hypothesis test ( t test , F test , and the correlation coefficient of determination ). The analysis showed that: (1) Capital Adequacy Ratio (CAR) but not significant positive effect on Lending. (2) Third Party Fund (DPK) positive and significant impact on the Lending. (3) Capital Adequacy Ratio (CAR) a significant negative effect on Return on Assets (ROA). (4) Third Party Fund (DPK) but not significant positive effect on Return on Assets (ROA). (5) Lending positive but not significant effect on Return on Assets (ROA). (6) Effect of Capital Adequacy Ratio (CAR) of the Return on Assets (ROA) greater than the influence of Capital Adequacy Ratio (CAR) of the Return on Assets (ROA) through Lending. (7) Effect of Third Party Fund (DPK) to Return on Assets (ROA) is smaller than the influence of Third Party Fund (DPK) to Return on Assets (ROA) through Lending.Keywords : Capital Adequacy Ratio, Return On Asset, Third Party Funds, Lending